A Solution to Two Paradoxes of International Capital Flows - Wei, Shang-Jin (IMF Working Papers; Working Paper ;, 2006)
International capital flows from rich to poor countries can be regarded as either too low (the Lucas paradox in a one-sector model) or too high (when compared with the logic of factor price equalization in a two-sector model). To resolve the paradoxes, we introduce a non-neoclassical model which features financial contracts and firm heterogeneity. In our model, free patterns of gross capital flow emerge as a function of the quality of the financial system and the level of protection for property rights(i.e., the risk of expropriation. A poor country with an inefficient financial system but a low expropriation risk may simultaneously experience an outflow of financial capital but an inflow of foreign direct investment (FDI), resulting in a small net flow.